Human rights and sexuality - reimagining the language of equality towards transformation in and through education - De Wet, A. (South African Journal of Higher Education, 2017)
For many years, arguments in favour of sexual minorities’ equality and sexuality rights have brought about legal reform worldwide. Although there are those who would contend that human rights and legal mechanisms associated with minorities could contribute to some positive experiences for sexual minorities, others have pointed out that legal reform brought about by the anti-discrimination laws does not necessarily result in a noticeable change in people’s discriminatory attitudes, nor does it automatically translate into lived experiences of equity for minority groups. Research in the education sector shows that despite promises of inclusion and non-discrimination brought about by human rights law, many education institutions “continue to reproduce patterns of heterosexism” (Francis and Msibi 2011, 160). Drawing from a project titled “Human Rights Literacy: A search for meaning”, the article explores how students in higher education institutions conceptualise sexual equality within a human rights discourse. Findings reported here indicate that the non-translation of legal rights into inclusion and equality for sexual minorities might be due to the gap between formal and substantive conceptualisations of equality. Acknowledgment of sexual minorities’ equal rights appears to be superficial while students seemingly lack an awareness of the gap between formal equality and substantive equality and the inequalities that play out in this gap. Against the background of sexual minorities’ unequal treatment and experiences, this article aims to re-imagine the language of equality towards equity for all sexualities in and through education.